If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying In(5x + -6) + In(x + -6) = In * 36 Reorder the terms: nI(-6 + 5x) + In(x + -6) = In * 36 (-6 * nI + 5x * nI) + In(x + -6) = In * 36 (-6nI + 5nxI) + In(x + -6) = In * 36 Reorder the terms: -6nI + 5nxI + nI(-6 + x) = In * 36 -6nI + 5nxI + (-6 * nI + x * nI) = In * 36 -6nI + 5nxI + (-6nI + nxI) = In * 36 Reorder the terms: -6nI + -6nI + 5nxI + nxI = In * 36 Combine like terms: -6nI + -6nI = -12nI -12nI + 5nxI + nxI = In * 36 Combine like terms: 5nxI + nxI = 6nxI -12nI + 6nxI = In * 36 Reorder the terms for easier multiplication: -12nI + 6nxI = 36nI Solving -12nI + 6nxI = 36nI Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36nI' to each side of the equation. -12nI + -36nI + 6nxI = 36nI + -36nI Combine like terms: -12nI + -36nI = -48nI -48nI + 6nxI = 36nI + -36nI Combine like terms: 36nI + -36nI = 0 -48nI + 6nxI = 0 Factor out the Greatest Common Factor (GCF), '6nI'. 6nI(-8 + x) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'nI' equal to zero and attempt to solve: Simplifying nI = 0 Solving nI = 0 Move all terms containing n to the left, all other terms to the right. Simplifying nI = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-8 + x)' equal to zero and attempt to solve: Simplifying -8 + x = 0 Solving -8 + x = 0 Move all terms containing n to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + x = 0 + 8 x = 0 + 8 Combine like terms: 0 + 8 = 8 x = 8 Add '-1x' to each side of the equation. x + -1x = 8 + -1x Combine like terms: x + -1x = 0 0 = 8 + -1x Simplifying 0 = 8 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 6(x-2)-(x-3)=5-4(10-x) | | 1y=7x^3+4x | | x+0.6*x=130 | | 9x^2-6x+106=0 | | (D^3-5D+8D-4)y=E^2X | | (4x+10)+4x+x=46 | | 3k^4-k^2-24=0 | | 4x-11=5x+10 | | -3-2.9=-9x-0.5 | | (X+3)(8-x)=0 | | x-11=3x-21 | | 6x+5x-3x=32 | | x^2-4x+y^2+6y+z^2+8z+4=0 | | 72°/180°=x/π | | X+1.2(0.8-X)=0.18 | | 320=3x*x | | 7x-x^2-6=0 | | 320=x+x | | 2*-12-5=-19 | | 54.3x*1.5=8(0.3x-3) | | 72c+6=164 | | 35x^2+150x+135=0 | | 7x^2+50x+27=0 | | 3y+60=2y | | (3u-5)(6-u)=0 | | 4x-9=3x-29 | | 4(x+1)-3(2x-4)=3(x-3) | | (1/25)*(3/35) | | 4x+3x=16*12 | | (24/17)/6 | | p=48-3q^2 | | (9/16)/3 |